Analysis of Investor’s Contentment towards Service Attribute of Dematerialized (DEMAT) Account of Nepal - Karki, Mahima (Nepalese Journal of Management Science and Research, 2024)
The intent of the study is to examine how content investors are with the attributes of service offered by Nepal’s dematerialized accounts. The term “Dematerialized Account” (abbreviated as “DEMAT account”) refers to a paperless or digital method of purchasing and selling stocks and other financial assets. Analysis of investor satisfaction with Nepal’s Dematerialized (DEMAT) Account Service Quality was the study’s primary goal. The study’s descriptive research design was utilized to gauge participant satisfaction with the level of service quality. The study discovered that the tangible component significantly affects investor satisfaction. Accordingly, the depository units should concentrate on the tangible aspect of service quality to ensure that investors are as satisfied as possible.